Literature Review: Development of Google Sites – Based Multimedia to Improve Elementary School Students’ Reading Literacy - Mulyaningsih, Titik; Hendratno, Hendratno; Subrata, Heru (IKIP Widya Darma Surabaya, 2023)
Objective: This study aims to determine the advantages and disadvantages of multimedia learning on Google Sites, content design, and effectiveness in improving reading literacy. Method: This research method is a review of literature from Scopus journals and Google Scholar in 2017 – 2023. The data analysis used in this study was qualitative descriptive. Results: The result of this study is that Google Sites has advantages in terms of ease of access and ease of use. Interesting content design can increase students' interest in reading. The limitation of Google Sites multimedia is the internet connection. Novelty: The novelty of this research is a review of the literature used from Google Scholar and Scopus so that the results can provide information on the success rate of developing Google Site-based multimedia in improving reading literacy. This makes the research relevant and has the potential to significantly contribute to the literature on reading literacy and the use of technology, particularly Google Sites in Basic Education.